Early diversification of sperm size in the evolutionary history of the old world leaf warblers (Phylloscopidae). (9th February 2016) - Supriya, K.; Rowe, M.; Laskemoen, T.; Mohan, D.; Price, T. D.; Lifjeld, J. T.
Abstract: Sperm morphological traits are highly variable among species and are commonly thought to evolve by post‐copulatory sexual selection. However, little is known about the evolutionary dynamics of sperm morphology, and whether rates of evolutionary change are variable over time and among taxonomic groups. Here, we examine sperm morphology from 21 species of Old World leaf warblers (Phylloscopidae), a group of generally dull, sexually monochromatic birds, which are known to have high levels of extra‐pair paternity. We found that sperm length differs markedly across species, spanning about 40% of the range observed across a larger selection of passerine birds. Furthermore, we found strong support for an 'early‐burst' model of trait evolution, implying that the majority of divergence in sperm length has occurred early in the evolutionary history of this clade with subsequent evolutionary stasis. This large early divergence matches the early divergence reported in ecological traits (i.e. body size and feeding behaviour). Our findings demonstrate that rates of evolution in sperm morphology can change over time in passerine taxa, and that evolutionary stasis in sperm traits can occur even in species exhibiting characteristics consistent with moderate‐to‐high levels of sperm competition. It remains a major challenge to identify the selection mechanisms and possible constraints responsible for these variable rates of sperm evolution.